The point (4,3) reflected about the x axis,

=> The x remains the same, the y flips over the x axis to be negative

(4,3) ==>> (4,-3)

The point (-3,-8) is reflected in the y-axis.

=> The y remains the same, the x flips over the y axis to be negative

(-3,-8)==>>(3,-8)

The point (2,4) is reflected in the line x = -3.

=> The x remains the same, the y flips over the x= -3 line.

Instead of reflecting over the x axis (or the x = 0) line

and just being +4 or 4 above the x axis to -4 or 4 below the x axis

you have +4 being 7 above the x= -3 line so you need

7 below the x= -3 line or -10 SO

(2,4)==>>(2,-10)

The point (a, b) is reflected in the line y = x

Consider that the line x=y is a 45 degree diagonal.

Imagine a point on the x axis at +3 i.e. (3,0)

Imagine a line perpendicular to x=y from the point (3,0)

(sorry there is no way to draw on here - try drawing it)

The line would hit the y axis at (0,3)

So you can see the x becomes y and y becomes x.

(a,b)==>>(b,a)

For

ΔXYZ is defined by its vertices X(1,3), Y(-3,5), and Z(0, -5).

ΔXYZ is reflected in the y-axis.

So for each of of the 3 points X, Y, and Z reflect them about

the y axis the same way in the second example above

and you will have the 3 new points X’, Y', and Z’

The translation T: (x, y) → (x -2, y + 4) maps the point (2, -3) to

The translation T: (x, y) → (x + 3, y - 2) maps the point (-4, -3) to

What you need to do here is just plug the values for X and Y into the translation.

e.g. for T: (x, y) → (x -2, y + 4) plug (2,-3) of x=2 y=-3 into (x -2, y + 4) and get the new values.